2017
DOI: 10.1159/000479869
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and IGF Delivered from Alginate Hydrogels Promote Stable Perfusion Recovery in Ischemic Hind Limbs of Aged Mice and Young Rabbits

Abstract: Biomaterial-based delivery of angiogenic growth factors restores perfusion more effectively than bolus delivery methods in rodent models of peripheral vascular disease, but the same success has not yet been demonstrated in clinically relevant studies of aged or large animals. These studies explore, in clinically relevant models, a therapeutic angiogenesis strategy for the treatment of peripheral vascular disease that overcomes the challenges encountered in previous clinical trials. Alginate hydrogels providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 45 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…To our knowledge, no other combination wound healing therapies involving a growth factor and anti-inflammatory have been investigated. Others have explored the dual delivery of VEGF-A with either PDGF-β, fibroblast growth factor-4, insulin growth factor-1, keratinocyte growth factor, epidermal growth factor, angiopoietin-1 or bone morphogenic protein-2 on the healing of cutaneous wounds, hind-limb ischemia and bone defects [78][79][80][81][82][83]. The impact of a fusion between IL-10 and IL-4 has also been explored in the treatment of neuro-inflammatory pain [84].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no other combination wound healing therapies involving a growth factor and anti-inflammatory have been investigated. Others have explored the dual delivery of VEGF-A with either PDGF-β, fibroblast growth factor-4, insulin growth factor-1, keratinocyte growth factor, epidermal growth factor, angiopoietin-1 or bone morphogenic protein-2 on the healing of cutaneous wounds, hind-limb ischemia and bone defects [78][79][80][81][82][83]. The impact of a fusion between IL-10 and IL-4 has also been explored in the treatment of neuro-inflammatory pain [84].…”
Section: Discussionmentioning
confidence: 99%
“… Biomaterial Growth Factor Comment Animal Model Delivery Method Ref. Alginate hydrogels VEGF and IGF In rabbits, the amount of growth factors was 2 orders of magnitude lower than the typical doses Enhanced perfusion recovery Female C57BL6/J mice: Young mice (8–10 weeks old); Middle-aged (13 months old); Old mice (20 months old); Female New Zealand White rabbits (2.5–3 kg) Mouse: Unilateral external iliac and femoral artery and vein ligation Rabbit: Ligation of the lateral circumflex artery, and the common, superficial and deep femoral arteries The area of the ligated vessels; Muscle tissue surrounding the vessel ligation site; Mouse: 50 μL; 3 μg VEGF and 3 μg IGF; Rabbit: 500 μL; 50 μL/injection; 20 μg VEGF and 20 μg IGF [ 62 ] Alginate hydrogels VEGF and SDF Factors were injected in the ischemic leg and were able to attract endothelial progenitors, that were systemically infused, to the ischemia site C57BL6/J mice for short-term recruitment studies; C.B-17 SCID mice for long-term healing Ligation of external iliac artery and vein Under the ligation site; 3 μg VEGF and 3 μg SDF [ 41 ] Nanoliposomal carrier with alginate hydrogels Glypican-1; Syndecan-4; FGF-2 Overcome growth factor resistance Wild-type mice or ob/ob mice (B6.Cg-Lepob/J); The ob/ob mice fed a high fat diet for 10 weeks The femoral artery separated from the femoral vein and nerve, and then double ligated and the artery severed at each ligation The region surrounding the femoral artery; 3 μg FGF-2 [ [48] , [49] , [50] , [51] ] Thiolated chitosan nanoparticles Secretoneurin Restored perfusion at the ischemia site Mice The left femoral artery exposed, ligated, and excised Thigh and calf muscles; Injection volume: 100 μL; 20 μL/injection; 5...…”
Section: Bioengineering Approaches For the Treatment Of Padmentioning
confidence: 99%
“…Promisingly, some experimental studies attempting angiogenic therapy in old and/or diabetic and/or hyperlipidemic animals with ischemic injury have demonstrated that it is possible to therapeutically induce blood vessel growth and remodeling also under these challenges (20,21,22,23,24). However, the functional gain to the ischemic territory may remain unsatisfactory despite increased vascularity, notably in human patients suffering from persistent vascular endothelial dysfunction, as demonstrated by impaired flow-mediated vasodilation (FMD).…”
Section: The Impact Of Vascular Endothelial Dysfunction On Angiogenicmentioning
confidence: 99%
“…Promisingly, we and others have shown that such combinatorial growth factor treatments allowed prevention of heart failure development in rats ( 40 ) and pigs ( 41 ). Of note, therapeutic angiogenesis approaches that have shown benefit in models of experimental ischemia in animals suffering from comorbidities have been based on such combinatorial treatments ( 20 , 22 , 23 , 24 , 42 ), indicating that this direction may indeed be the way to go to successfully bridge the translational bench-to-bed gap. However, in patients with refractory angina, intramyocardial dual delivery of VEGF-A and FGF-2 failed to increase perfusion, likely due to the use of plasmids rather than viral vectors for delivery ( 43 ).…”
Section: Evolving Approaches For Therapeutic Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation